1992
DOI: 10.1016/0014-5793(92)80598-b
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of murein peptidase activity and AmpC β‐lactamase synthesis in Escherichia coli

Abstract: In the periplasmic space of F.sche~'ichia coil, the (L)-m-A,pm-(D)-m-A,pm pcptid¢, the lipoprotein, and the AmpC fl-lactamas¢ are controlled by growth rate. To explain this coordinate regulation, it is proposed that the AmpC protein functions as an LD-endopeptidase in addition to its known function as a fl-lactamas¢. As LD-peptides, vo-peptides and fl-lactams are structurally similar, to-peptidases may belong to the larger family of DD-peptidases and serine ~-lactamases. In contrast to K coll. many related bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…It has been proposed that structural similarities between both substrate (the b-lactam antibiotics vs. D-Ala-D-Ala peptidoglycan side chain) and enzyme (class A and C b-lactamases vs. DD-peptidases) could indicate an in vivo interaction of b-lactamases with cellwall components (Bishop and Weiner 1992;Morosini et al 2000). Marginal peptidase activity of b-lactamases as well as b-lactamase activity of DD-peptidases has been described in vitro (Rhazi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that structural similarities between both substrate (the b-lactam antibiotics vs. D-Ala-D-Ala peptidoglycan side chain) and enzyme (class A and C b-lactamases vs. DD-peptidases) could indicate an in vivo interaction of b-lactamases with cellwall components (Bishop and Weiner 1992;Morosini et al 2000). Marginal peptidase activity of b-lactamases as well as b-lactamase activity of DD-peptidases has been described in vitro (Rhazi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized, however, that class C b-lactamases could participate in recycling of cell-wall components due to the structural similarity between b-lactam antibiotics and the DD-peptide bond found in the peptidoglycan layer (Bishop and Weiner 1992). A fitness cost associated with expression of the class C b-lactamase AmpC from Enterobacter cloacae in Salmonella enterica serotype Typhimurium has been documented (Morosini et al 2000).…”
mentioning
confidence: 99%
“…Interestingly, at least two Shigella species, S. flexneri and S. dysenteriae, also lack the ampC gene, as demonstrated by Maurelli et al (25). The presence of the ampC gene, together with its exquisite transcriptional regulation (19) in most enterobacterial species, has suggested that AmpC might be involved in cell wall recycling (3).…”
mentioning
confidence: 97%
“…The AmpD, PbpA and FtsZ gene products control aspects of cell-wall metabolism, whereas the AmpE and AmpG proteins share amino-acidsequence similarities with various membrane transport proteins (reviewed in Bishop and Weiner, 1992). Additionally, mutations in the ampR gene can suppress the ampG mutation, which suggests that the AmpR and AmpG proteins may interact physically (Bartowsky and Normark, 1991).…”
mentioning
confidence: 99%